Determinación de sodio , cloro,potasio y su relación con la deshidratación en infantes con gastroenteritis que se atienden en el Hospital Teófilo Dávila mediante el método luminiscencia,del Cantón Machala 2014. - Zambrano Zambrano, Leticia Johanna (2015)
Gastroenteritis an inflammation or infection of the gastric and intestinal mucosa in response to various damages , whose severity ranges from mild illness to compromise the life of the infant. A diagnostic confirmation of gastroenteritis is the loss of fluids causing dehydration and thus the loss of electrolytes the same which is caused by various symptoms such as vomiting , diarrhea , fever .